Neutrophil to lymphocyte ratio and in-hospital mortality among patients with SARS-CoV-2: A retrospective study. (October 2022) - Al-Mazedi, Maryam Salah; Rajan, Rajesh; Al-Jarallah, Mohammed; Dashti, Raja; Al Saber, Ahmad; Pan, Jiazhu; Zhanna, Kobalava D.; Abdelnaby, Hassan; Aboelhassan, Wael; Almutairi, Farah; Alotaibi, Naser; Al Saleh, Mohammad; et al.
Abstract: The goal of this study was to investigate in-hospital mortality in patients suffering from acute respiratory syndrome coronavirus 2 (SARS-CoV-2) relative to the neutrophil to lymphocyte ratio (NLR) and to determine if there are gender disparities in outcome. Between February 26 and September 8, 2020, patients having SARS-CoV-2 infection were enrolled in this retrospective cohort research, which was categorized by NLR levels ≥9 and < 9. In total, 6893 patients were involved included of whom6591 had NLR <9, and 302 had NLR ≥9. The age of most of the patients in the NLR<9 group was 50 years, on the other hand, the age of most of the NLR ≥9 group patients was between 50 and 70 years. The majority of patients in both groups were male 2211 (66.1%). The ICU admission time and mortality rate for the patients with NLR ≥9 was significantly higher compared to patients with NLR <9. Logistic regression's outcome indicated that NLR ≥9 (odds ratio (OR), 24.9; 95% confidence interval (CI): 15.5–40.0; p  < 0.001), male sex (OR, 3.5; 95% CI: 2.0–5.9; p  < 0.001) and haemoglobin (HB) (OR, 0.95; 95% CI; 0.94–0.96; p  < 0.001) predicted in-hospital mortality significantly. Additionally, Cox proportional hazards analysis (B = 4.04, SE = 0.18, HR = 56.89, p < 0.001) and Kaplan–Meier survival probability plots also indicated that NLR>9 had a significant effect on mortality. NLR ≥9 is an independent predictor of mortality(in-hospital) among SARS-CoV-2 patients. Highlights: The main finding of this study is that NLR is an autonomous predictor of in-hospital mortality in patients with SARS-CoV-2. Fatality in SARS-CoV-2 patients with NLR >9 was 25 times higher than that in patients with NLR <9. Patients with NLR >9, the average length of ICU stay was higher. Mortality rate in males was high compared to females with NLR>9.